Perlindungan Hukum dan Pemulihan Hak Pemilik Tanah pada Sengketa Kesalahan Penggarapan Lahan Secara Perdata - Tri Auli; Mulida Hayati; Hilyatul Asfia; F.X Ary Setiawan (Jurnal Hukum Lex Generalis, 2026)
Land disputes resulting from improper cultivation by plantation companies often cause material and immaterial losses to the rightful landowners. A case in Waringin Agung Village demonstrates that PT Karya Makmur Bahagia (KMB) cultivated residents’ land without legal basis, thereby damaging crops that serve as the community’s livelihood. This study aims to analyze legal protections and mechanisms for restoring landowners’ rights through civil proceedings. The method employed is normative legal research using a legislative and conceptual approach, drawing on primary legal sources such as the Civil Code and the Land Law, supported by scholarly literature. The research results show that unauthorized land acquisition and cultivation by companies can be categorized as land grabbing, which has criminal consequences. In addition to requiring compensation from the landowner, the perpetrators can also be subject to criminal sanctions in accordance with applicable laws and regulations. Legal protection for landowners can be achieved through both litigation and nonlitigation efforts.